Kontrol Keamanan Sistem Informasi Akuntansi Bank Perkreditan Rakyat (BPR) Sumatera Barat - Sulastri, Sulastri (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT - SEKOLAH TINGGI ILMU EKONOMI SAKTI ALAM KERINCI, 2018)
This study aims to determine the security control of accounting information systems that exist in West Sumatra Rural Banks. The study was conducted on 91 rural banks in the province of West Sumatra, but only 41 returned questionnaires. The results of the study show that the BPR has implemented the security control of the accounting information system well